1989
DOI: 10.1016/0014-5793(89)80679-9
|View full text |Cite
|
Sign up to set email alerts
|

Independence of triacylglycerol‐containing compartments in cultured fibroblasts from Wolman disease and multisystemic lipid storage myopathy

Abstract: The functional relationship between the two subcellular compartments involved in catabolism of triglycerides, i.e. lysosomes and lipid-containing cytoplasmic vacuoles, has been investigated using cultured fibroblasts from patients affected with two different genetic lipid (triacylglycerol) storage disorders: Wolman disease and multisystemic lipid storage myopathy. As shown by metabolic studies in intact cultured cells, lysosomal degradation of exogenous labelled triacylglycerols (incorporated into lipoproteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…The accrual of neutral lipids was shown not to be caused by a defect in mitochondrial fatty acid (FA) uptake or defective ␤-oxidation (42,60). Also, enzymatic activities of lipases, carboxyesterases (25,48,59,60), and enzymes for the glycerolipid synthesis (24,59) were normal in most studies. Hilaire et al (22), however, observed an impaired degradation of TG containing long-chain FA in NLSD cells, suggesting a defect in long-chain TG hydrolase activity.…”
Section: Mutations In Cgi-58 Cause Nlsd With Ichthyosismentioning
confidence: 93%
“…The accrual of neutral lipids was shown not to be caused by a defect in mitochondrial fatty acid (FA) uptake or defective ␤-oxidation (42,60). Also, enzymatic activities of lipases, carboxyesterases (25,48,59,60), and enzymes for the glycerolipid synthesis (24,59) were normal in most studies. Hilaire et al (22), however, observed an impaired degradation of TG containing long-chain FA in NLSD cells, suggesting a defect in long-chain TG hydrolase activity.…”
Section: Mutations In Cgi-58 Cause Nlsd With Ichthyosismentioning
confidence: 93%
“…Several elegant studies done using fibroblasts derived from CDS patients demonstrated that the excess TG accumulation in these cells did not result from augmented fatty acid uptake or TG synthesis rates (19,20). Instead, fibroblasts from CDS patients seem to lack the ability to hydrolyze stored TG, even though cellular lipase and carboxylesterase activities are normal (20)(21)(22). As a result of this paradoxical finding, it has been speculated that TG lipases in these cells may be missing some critical cofactor, be mislocalized, or be unable to gain access to the LD surface (23,24).…”
mentioning
confidence: 99%
“…In human fibroblasts, triacylglycerols are degraded in two separate and independent subcellular (lysosomal and cytoplasmic non-lysosomal) compartments (1). In the lysosomal compartment, triacylglycerols and cholesteryl esters of low density lipoprotein and very low density lipoprotein taken up by cells are degraded by the acid lysosomal lipase (2,3), which is genetically deficient in Wolman disease (4).…”
mentioning
confidence: 99%
“…In the lysosomal compartment, triacylglycerols and cholesteryl esters of low density lipoprotein and very low density lipoprotein taken up by cells are degraded by the acid lysosomal lipase (2,3), which is genetically deficient in Wolman disease (4). In the cytoplasmic compartment of fibroblasts, triacylglycerols are degraded by a lipase system (yet poorly characterized) different from the other known cellular (hormone-sensitive lipase) or secretory lipases (1,5) and different from the cholesteryl ester degradation pathway (6). As shown by using radiolabeled oleic acid or pyrene-containing fluorescent fatty acids, this degradative pathway of cytoplasmic triacylglycerols is deficient in the neutral lipid storage disease (NLSD) 1 (1, 5, 7-10), a rare inherited metabolic disease generally characterized by the association of muscular weakness, ichthyosis, and multisystemic triacylglycerol storage (11,12).…”
mentioning
confidence: 99%